Fluorescent and nonlinear optical features of CdTe quantum dots - A. A., Umar; Ali Hussain, Reshak, Prof. Dr.; Oyama, M.; Plucinski, K. J. (Springer Science+Business Media, LLC., 2012)
Link to publisher's homepage at www.springerlink.com